Research Status of CPM for Satellite-Terrestrial Integrated Network - Zihao PAN; Chen XIE; Heng WANG; Daoxing GUO (天地一体化信息网络)
Around the vision of ＆quot;full coverage＆quot; of the new generation of mobile communication system (6G), satelliteterrestrial integration, as one of the key technologies, is the development direction of the future wireless communication system.The construction of satellite-terrestrial integration network and deep integration need reasonable waveforms at physical layer.In view of the problems of transmission in satellite-terrestrial integration, the signifi cant advantages and practicability of continuous phase modulation (CPM) signal in spectral effi ciency and energy effi ciency were analyzed.The research progress of CPM signal at receiver in mobile communication system from the time and frequency domain were discussed, which provided support for CPM related research in satellite-terrestrial integration in the future.